2023
DOI: 10.1200/jco.2023.41.4_suppl.140
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 2 study of trastuzumab and pertuzumab (TP) compared to cetuximab and irinotecan (CETIRI) in advanced/metastatic colorectal cancer (mCRC) with HER2 amplification: SWOG S1613.

Abstract: 140 Background: HER2 ( ERBB2) over-expression and amplification (HER2+) is seen in a small but distinct subset (2-3%) of mCRC and is enriched in RAS/BRAF wild type (WT) tumors. This subset is characterized by a limited response to anti-epidermal growth factor receptor monoclonal antibody-based (anti-EGFR) therapy and a promising response to dual-HER2 inhibition. Methods: In this multicenter, open label, randomized, phase 2 trial, we enrolled 54 patients with RAS/BRAF WT HER2+ mCRC who had had disease progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In nonrandomized trials, dual HER2 blockade showed promising activity in patients with previously treated HER2 + metastatic colorectal cancer. However, the recently reported SWOG S1613 randomized phase II trial failed to show the superiority of a trastuzumab plus pertuzumab chemo-free regimen compared with irinotecan plus cetuximab as second- or third-line treatment in patients with HER2 + , RAS and BRAF WT disease ( 18 ). Although these results may have been influenced by the small sample size and the lack of prior irinotecan exposure in about half of the patients, this study confirms that a nonnegligible proportion of patients do not derive benefit from anti-HER2–targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In nonrandomized trials, dual HER2 blockade showed promising activity in patients with previously treated HER2 + metastatic colorectal cancer. However, the recently reported SWOG S1613 randomized phase II trial failed to show the superiority of a trastuzumab plus pertuzumab chemo-free regimen compared with irinotecan plus cetuximab as second- or third-line treatment in patients with HER2 + , RAS and BRAF WT disease ( 18 ). Although these results may have been influenced by the small sample size and the lack of prior irinotecan exposure in about half of the patients, this study confirms that a nonnegligible proportion of patients do not derive benefit from anti-HER2–targeted therapy.…”
Section: Discussionmentioning
confidence: 99%